Evidence of shark-on-shark trophic interactions in the Miocene of Costa Rica, Southern Central America - Araya-Gamboa, Daniela (2026)
The trophic interactions of many extant shark species are well known. When examining the fossil record, the evidence is weak, often indirect, and subject to interpretation, almost always limited to bite marks on bones. However, the record of shark teeth embedded in skeletal remains, although rare in the fossil record, constitutes direct evidence of predation and/or scavenging. Even rarer is the record of trophic interactions type Shark-on-Shark. Here, we describe the discovery of a fossil that provides direct evidence of trophic interaction between a Hemigaleid shark on Carcharhinid shark, from inner neritic sediments of the Santa Teresa Formation of Miocene age.